2018
DOI: 10.1039/c8cp04727h
|View full text |Cite
|
Sign up to set email alerts
|

Multiple binding modes of a moderate ice-binding protein from a polar microalga

Abstract: Ice-binding proteins (IBPs) produced by cold-tolerant organisms interact with ice and strongly control crystal growth. The molecular basis for the different magnitudes of activity displayed by various IBPs (moderate and hyperactive) has not yet been clarified. Previous studies questioned whether the moderate activity of some IBPs relies on their weaker binding modus to the ice surface, compared to hyperactive IBPs, rather than relying on binding only to selected faces of the ice crystal. We present the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…This binding pattern to ice crystal planes was confirmed also for the moderate IBP isoform 11 from the sea‐ice diatom Fragilariopsis cylindrus ( fc IBP11) by laser confocal fluorescence microscopy of a single ice crystal in a solution of the fluorescently labelled protein . In addition to these experimental methods, MD simulations of fc IBP11 indicated that the protein can, at least partly, bind the primary prism and basal faces, despite its moderate activity .…”
Section: Activity Of Duf3494 Ibpsmentioning
confidence: 65%
See 4 more Smart Citations
“…This binding pattern to ice crystal planes was confirmed also for the moderate IBP isoform 11 from the sea‐ice diatom Fragilariopsis cylindrus ( fc IBP11) by laser confocal fluorescence microscopy of a single ice crystal in a solution of the fluorescently labelled protein . In addition to these experimental methods, MD simulations of fc IBP11 indicated that the protein can, at least partly, bind the primary prism and basal faces, despite its moderate activity .…”
Section: Activity Of Duf3494 Ibpsmentioning
confidence: 65%
“…A) being the most representative (~ 68%). Almost all characterized DUF3494 IBPs exhibit this simple architecture . Generally, single‐DUF3494 IBPs also contain an N‐terminal signal peptide, suggesting that these proteins are secreted into the environment near the cells or accumulate in the membrane .…”
Section: Architecture Of Duf3494 Ibpsmentioning
confidence: 99%
See 3 more Smart Citations